RACNet: A High-Fidelity Data Center Sensing Network - Liang, Chieh-Jan Mike; Liu, Jie; Luo, Liqian; Terzis, Andreas; Zhao, Feng (SenSys (ACM Conference on Embedded Network Sensor Systems), 2009)
RACNet is a sensor network for monitoring a data center’s environmental conditions. The high spatial and temporal fidelity measurements that RACNet provides can be used to improve the data center’s safety and energy efficiency. RACNet overcomes the network’s large scale and density and the data center’s harsh RF environment to achieve data yields of 99% or higher over a wide range of network sizes and sampling frequencies. It does so through a novel Wireless Reliable Acquisition Protocol (WRAP). WRAP decouples topology control from data collection and implements a token passing mechanism to provide network-wide arbitration. This congestion avoidance philosophy is conceptually different from existing congestion control algorithms that retroactively respond to congestion. Furthermore, WRAP adaptively distributes nodes among multiple frequency channels to balance load and lower data latency. Results from two testbeds and an ongoing production data center deployment indicate that RACNet outperforms previous data collection systems, especially as network load increases.